1988
DOI: 10.1002/1097-0142(19880815)62:4<806::aid-cncr2820620428>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of malignant pleural effusions with intracavitary corynebacterium parvum

Abstract: Fifty-three cases of metastatic pleural effusion (30 haemorragic and 23 serofibrinous) were treated with 4 mg of Corynebacterium parvum (CP) injected weekly into the pleural cavity after total thoracentesis. Of the 53 effusions, 24 were metastases from lung cancer and 29 from breast cancer. Complete response (CR) was assessed as total resolution of pleural effusion after explorative thoracentesis. The results were as follows: 15 CR after two injections of CP, 30 CR after three, and 5 CR after the fourth admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Of note, a significant difference exists regarding the role of NCPP and CP in stimulating IFN-γ and TNF-α secretion, i.e., NCPP could activate macrophages to secrete a higher level of IFN-γ than CP ( p b 0.05), whereas CP could induce higher TNF-α secretion than NCPP ( p b 0.05), suggesting that NCPP may not induce fibrosis through the distinct immunoregulatory mechanism in stimulating specific cytokine secretion. Recent observations indicated that IFN-γ was a powerful anti-fibrogenic cytokine that might play central roles in the downregulation of liver fibrosis, whereas TNF-α might aggravate this disease by influencing the balance of IFN-γ [35,36]. The role of NCPP from this study is, at least in part, in agreement with these conclusions.…”
Section: Discussionsupporting
confidence: 89%
“…Of note, a significant difference exists regarding the role of NCPP and CP in stimulating IFN-γ and TNF-α secretion, i.e., NCPP could activate macrophages to secrete a higher level of IFN-γ than CP ( p b 0.05), whereas CP could induce higher TNF-α secretion than NCPP ( p b 0.05), suggesting that NCPP may not induce fibrosis through the distinct immunoregulatory mechanism in stimulating specific cytokine secretion. Recent observations indicated that IFN-γ was a powerful anti-fibrogenic cytokine that might play central roles in the downregulation of liver fibrosis, whereas TNF-α might aggravate this disease by influencing the balance of IFN-γ [35,36]. The role of NCPP from this study is, at least in part, in agreement with these conclusions.…”
Section: Discussionsupporting
confidence: 89%
“…This explanation appears unlikely to us. Although the range in the dose of C. parvum has been wide, varying from 4 mg used by CASALI et al [16] to 21 mg used by CURRIE et al [17], the majority of the authors have used a dose of 7 mg [4,[18][19][20]. Therefore, if C. parvum was going to be effective, one would consider that a dose of 8 mg should be sufficient.…”
Section: -Macroscopic Examination Of the Right Sidementioning
confidence: 99%
“…The treatment of MPEs with bacterial preparations and cytokines, such as IFN-␣ and IFN-␤, has been reported. 41,42 It has been demonstrated that the daily intrapleural administration of IL-2 results in the in vivo generation of killer activity of mononuclear cells in the MPE, leading to an effective clinical control. 43 Several treatment modalities are currently available for patients with MPEs.…”
Section: Malignant Pleural Effusionsmentioning
confidence: 99%